PERAN SOSIAL DOMESTIK PEREMPUAN DALAM TAFSIR IBN KATSIR Sebuah Tinjauan Hermeneutik - Agustina, Arifah Millati (Ahkam: Jurnal Hukum Islam, 2016)
In understanding a text, of which focus is to find meaning in an openand comprehensive meaning, it needs to take into account not onlyliteral but also moral ideas. The effort needs to be done to revive thedestination stored in the one of the methods used by contemporarycommentators is Hermeneutics. In this article the writer employshistory analysis (Historically effected consciousness) and preunderstanding(Vorverstandnis) to understand the text. On the basis ofthe use of the theory of hermeneutics, the writer applies these theoriesin defining gender topics. Selection of gender topics is based on theconsideration that many laws that do not contain moral ideas as aresult of the reading of the text. The application of the two analysesabove will result in objective interpretations as the meaning of textwhich is intended by its commentators.Kata kunci: Peran Sosial Domestik, Perempuan, Tafsir Ibn Katsir